The longitudinal associations between perceived importance of the internet and depressive symptoms among a sample of Chinese adults - Zhengyu Wu; Jiabo Zhang; Maomin Jiang; Jiawen Zhang; Ye-Wei Xiao (Frontiers Media S.A., 2023)
ObjectiveThe aim of this study is to examine the extent to which individuals' cognitive evaluation of the importance of the Internet is associated with depressive symptoms, and in what ways.MethodsThis study utilized a sample of 4,100 participants from the fourth (2016), fifth (2018), and sixth (2020) waves of the China Family Panel Studies. Structural equation modeling was employed for data analysis.ResultThe findings of this study reveal that individuals' cognitive evaluation of the importance of the Internet in 2016 was positively linked with the frequency of Internet use and subjective socioeconomic status in 2018. Furthermore, the frequency of Internet use and subjective socioeconomic status in 2018 were found to be negatively associated with depressive symptoms in 2020. These results indicate that the perceived importance of the Internet has an indirect effect on depressive symptoms through the identified pathway.ConclusionThe present findings contribute to the existing literature by highlighting the importance of individuals' perceived importance of the internet as a significant factor that influences depressive symptoms. The results suggest that policy makers should take actions to increase public awareness of the importance of the Internet in the digital era, and to ensure equitable access to the internet, thus facilitating convenient internet use and helping individuals adapt to the digital age.